1980
DOI: 10.1002/1097-0142(19801201)46:11<2389::aid-cncr2820461114>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy of advanced prostatic cancer with adriamycin, BCNU, and cyclophosphamide

Abstract: A phase II trial of Adriamycin, BCNU, and cyclophosphamide was performed in 29 patients with advanced prostatic carcinoma (Southeastern Cancer Study Group protocol SEG 76 PR 0102P). Therapy consisted of BCNU 100 mg/m2, plus cyclophosphamide, 300 mg/m2 i.v., on day 1, followed by Adriamycin, 30 mg/m2 i.v., on day 2. Therapy was repeated every four weeks. In 27 evaluable patients refractory to prior estrogen therapy, one patient had a complete response, six patients had partial responses, and two patients had ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Such Gly-I inactivation may then help overcome drug resistance, leading to growth cessation and/or cell death in prostatic cancer cells. Moreover, clinical trials of BCNU on patients with PC were conducted more than 20 years ago (Presant et al, 1976(Presant et al, , 1980, and showed some promising outcomes. However, because no further studies have been reported since then, it is worthwhile to resume the investigation of BCNU to reevaluate its efficacy on prostatic cancer cells and to explore its cytotoxic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Such Gly-I inactivation may then help overcome drug resistance, leading to growth cessation and/or cell death in prostatic cancer cells. Moreover, clinical trials of BCNU on patients with PC were conducted more than 20 years ago (Presant et al, 1976(Presant et al, , 1980, and showed some promising outcomes. However, because no further studies have been reported since then, it is worthwhile to resume the investigation of BCNU to reevaluate its efficacy on prostatic cancer cells and to explore its cytotoxic mechanism.…”
Section: Introductionmentioning
confidence: 99%